Evolution of Massive Population III Stars - Sung-Chul Yoon (Acta Polytechnica CTU Proceedings, 2014)
While the evolution of massive stars in the local Universe is dominated by mass-loss, the evolution of massive Population III stars should be dominated by rotation. An important effect of rotation is rotationally-induced chemical mixing that can dramatically change the stellar structure and the nucleosynthesis. This has significant consequences in the predicted explosion types of Population III stars.